Sensitivity of Louvers in Opening Angle and Profile on Daylighting and Natural Ventilation in Tropical Vertical Housing - Anggun Puspita Jahja; Asri Dinapradipta; F.X. Teddy Badai Samodra (Riviera Publishing, 2026)
Vertical housing in warm humid tropics requires façade strategies that balance daylight and natural ventilation. External louvers are commonly used, yet empirical evidence on the sensitivity of design variables especially opening angle and profile remains limited. This research aims to evaluate the sensitivity of trapezoidal louvre configurations in balancing daylighting and ventilation performance in the critical west-facing orientation of tropical vertical housing. A paired physical experiment was conducted using two identical mock-up rooms at Eco House ITS, Surabaya: one untreated base case and one equipped with louvers. Three louver profiles and three opening angles (45°, 60°, and 90°) were tested. Indoor illuminance, air velocity, and air temperature were recorded at multiple interior points and an outdoor reference at 10-minute intervals. The analysis applied paired comparisons against the base case and two-way ANOVA to quantify the sensitivity of design variables. The results show that all louver configurations reduced indoor illuminance by 61.0–77.1%. Model 2 at 45° retained the highest proportion of useful daylight (42.7% above 300 lux), while Model 2 at 60° achieved the highest daylight factor (4.36%). In terms of ventilation, only Model 1 at 45° slightly increased indoor air velocity (+0.016 m/s), whereas all configurations reduced indoor temperature (0.432–0.663°C). Sensitivity analysis indicates that the opening angle is the dominant factor influencing daylight (78.1%), air velocity (54.7%), and temperature (50.4%). The study concludes that louver design should prioritize opening angle selection before refining profile geometry, providing empirical evidence for façade strategies that balance daylight control and natural ventilation in tropical vertical housing.